'We are not infertile': challenges and limitations faced by women in same-sex relationships when seeking conception services in São Paulo, Brazil. Issue 11 (2nd November 2019) - Carvalho, Paula Galdino Cardin de; Cabral, Cristiane da Silva; Ferguson, Laura; Gruskin, Sofia; Diniz, Carmen Simone Grilo
Abstract: The use of reproductive technologies has expanded beyond cases of infertility, and opportunities for individuals of different sexual orientations to use such technologies for conception have increased. The authors examined the challenges and limitations faced by women in same-sex relationships seeking conception services in São Paulo, Brazil. They interviewed 16 women in same-sex relationships who conceived children using reproductive technologies. Access to public health services for conception remains limited and exclusive to infertile heterosexual couples. Women in same-sex relationships are forced to select between costly medical treatments in the private sector, or self-insemination with sperm from a known donor. In this study, individuals reported that they experienced adverse effects of treatments; were treated with technologies for infertility when they were, in fact, fertile; and were exposed to unnecessary and invasive interventions. Growing political conservatism and the reduction of investment in public health services are factors that can directly affect sexual and reproductive health, including that of lesbians. Public policies that enable same-sex couples to conceive have yet to be developed in many countries, and a clearer articulation of the right to evidence-informed, rights-based care, consistent with national and international guidelines is a much-needed next step.